ANALYSIS OF THE CHEMICAL COMPOSITION OF SURFACE TRIBOFILMS FORMED IN LOCAL CONTACT OF GEAR TRANSMISSIONS AFTER RUNNING IN AN OIL ENVIRONMENT WITH CARBONFLUORIDE ADDITIVES - Melnyk, Volodymyr; Leusenko, Darya; Radko, Oleh (Problems of Friction and Wear, 2025)
The content of chemical elements and their distribution along the depth of organic films of SOP for industrial oils of the ITD series of different viscosities without additives and with chemically active additives were determined by bombardment OGE spectroscopy methods. SOP films are formed more intensively under friction conditions, in an environment with a more viscous oil, and contain a greater amount of carbon and oxygen. By methods of metallophysical analysis of surfaces, after friction in CF-containing environments, CF2/CF3 groups and also metal fluoride compounds of the MeF3 type were detected in the surface layer. Moreover, the former, having a shielding effect, localize shear deformations, as a result of which friction losses of contacting surfaces are significantly reduced, and the latter increase the anti-wear and anti-seize properties of friction pairs, due to the formation of an anti-wear surface layer chemically modified with fluorine to a depth of about 5 microns.